Challenges of Implementing Packaging Design in Rural Food Entrepreneurship Owned by Underprivileged Women – A Case Study - Shaharuddin, Siti Shukhaila; Manaf, Ahmad Azaini Abdul (Journal of Graphic Engineering and Design, 2024)
This project was implemented to help low-income and underprivileged women grow their small businesses. This project aims to identify and analyse the problems faced by underprivileged women, focusing on food packaging. The participants were from Kampung Pinggan Jaya, Kuching Sarawak in Malaysia, who run small and medium food businesses. The food categories were based on dry and frozen foods, which were mainly homemade. The participants were housewives aged between 30 and 45 years with low monthly household incomes ranging from US $45 (MYR 200) to US $168 (MYR 750). Thus, the project's main objective is to improve product packaging to establish itself in the local market. Empathy mapping was the technique of choice as it demonstrates collaborative visualisation. Consequently, an entrepreneurship workshop was organised to identify potential products and participants interested in the project. Some problems and constraints during project implementation were due to financial concerns, attitudes, and illiteracy.